Future-Proofing German–Chinese Partnerships in Higher Education - Wahlers, Marijke (International Higher Education, 2021)
Building on solid, long-term cooperation, it is now time to future-proof German–Chinese university collaboration. Taking a nuanced view of the specific parameters, objectives, and content of individual partnerships is key. Open dialogue on opportunities and challenges—both within one’s own university and with partner institutions—will help clarify matters and identify development pathways. The German Rectors' Conference’s guiding questions on university partnerships with China are intended to support and enhance this dialogue.